Delays in Arterio-Venous Fistula Formation Among Patients With Chronic Kidney Disease; A Comparative Analysis Between Patient and Healthcare Related Factorstween Patient and Healthcare Related Factors - Javaid, Muhammad Arslan; Baig, Zahid Farooq; Ahmed, Nisar; Tanseer, Ubaid; Javed, Muhammad Arslan; Siddique, Muhammad (Pakistan Armed Forces Medical Journal, 2024)
Objective: To evaluate the factors associated with delay in arterio-venous fistula formation among the patients with chronic kidney disease on hemodialysis. Study Design: Comparative cross-sectional study. Place and Duration of Study: Combined Military Hospital, Lahore Pakistan, from Jan to Dec 2020. Methodology: All patients above 18 years of age with chronic kidney disease on maintenance hemodialysis (end stage renal disease) were inducted in the study. Patients requiring hemodialysis for acute kidney injury were excluded from the study. Patients were interviewed face-to-face about their socio-demographic variables, cause of delay and mean delay time from diagnosis to Arterio-venous fistula formation. Results: Out of 292 patients, 228 patients (76%) had a delay in arterio-venous fistula and first dialysis through double lumen catheter. The mean age of these patients was 59.05 years with 78.1% males. The mean delay of these patients was 60.63+26.832 days. Patient unwillingness and lack of awareness of deteriorating renal disease were the commonest factors (35%) in patient related factors and delayed surgical appointment being commonest (49.1%) in health care associated factors. The longest delay time was 69.04±25.759 months which was associated with delayed surgical appointment (p<0.001). Monthly income, gender and age had significant impact on different factors included in this study. Conclusion: The study identified that differences in Arterio-venous fistula maturation with respect to age, gender and socio-demographic factors were significant. Timely formation of Arterio-venous fistula in patients with chronic kidney disease is the most favourable approach to establish vascular access for hemodialysis and improves outcome.